Preface to the special issue on Formal Approaches to Parallel and Distributed Systems 2018 - Loulergue, Frédéric (Journal of logical and algebraic methods in programming, 2020)
This special issue contains extended versions of selected papers from the 5th International Symposium on Formal Approaches to Parallel and Distributed Systems (4PAD 2018). The symposium was held in Orléans, France on July 19th, 2020 in conjunction with the 2018 International Conference on High Performance Computing & Simulation (HPCS 2018).